2016
DOI: 10.1155/2016/7172920
|View full text |Cite
|
Sign up to set email alerts
|

Dexmedetomidine versus Magnesium Sulfate as Adjunct during Anesthesia for Laparoscopic Colectomy

Abstract: Objectives. To compare dexmedetomidine versus magnesium during laparoscopic colectomy. Patients and Methods. 51 patients were randomly allocated into 3 groups: group C (control) received saline infusion, group D dexmedetomidine 1 g/kg and then 0.4 g/kg/hr, and group M MgSO4 2 g and then 15 g/kg/min. Intraoperative hemodynamics were measured before and 1 min after intubation (T1 and T2), before and 5 min after peritoneal insufflation (T3 and T4), before and 5 min after 30° Trendelenburg position (T5 and T6), 5 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 19 publications
0
21
0
Order By: Relevance
“…And then 4 studies were excluded by full-text review for they were performed in pediatric patients. At last, 10 RCTs were enrolled in further meta-analysis [14][15][16][17][18][19][20][21][22][23]. The identification procedure of these eligible articles is described in Fig 1. The enrolled studies were published from 2011 to 2018, and all of them were published in English.…”
Section: Literature Search Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…And then 4 studies were excluded by full-text review for they were performed in pediatric patients. At last, 10 RCTs were enrolled in further meta-analysis [14][15][16][17][18][19][20][21][22][23]. The identification procedure of these eligible articles is described in Fig 1. The enrolled studies were published from 2011 to 2018, and all of them were published in English.…”
Section: Literature Search Resultsmentioning
confidence: 99%
“…A total of 663 patients were randomized to receive two drugs. In 10 included RCTs, 5 were researches about head and neck surgery [14][15][16][17][18], 3 were researches about spinal surgery [19][20][21], and the rest two trials were researches about pituitary adenoma surgery [22] and laparoscopic colorectal resection surgery [23]. All enrolled studies reported the hemodynamic parameters (MAP, HR), and 6 studies reported the evaluation of surgical field bleeding by using 6-point scale [14][15][16][17][18]22].…”
Section: Basic Characteristics Of Enrolled Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…During pneumoperitoneum for operative laparoscopy, impairment of hemodynamic status occurs mainly at the beginning of peritoneal insufflation [2]. It is well known that elevated intrapleural pressure significantly reduces the venous return and the circulating blood volume, which induces the elevated levels of vasopressin [1,2,10]. Adrenergic receptor blockers, calcium channel blockers, opioids, and vasodilators are routinely used to attenuate the pneumoperitoneum-related hemodynamic instability, but they are all accompanied with varying degrees of reduction in CO.…”
Section: Resultsmentioning
confidence: 99%